Turtle Moon - Hannah Gold (India Harper Collins, 2024)
Under the hot tropical sun, Silver settles into life at the animal centre. She even witnesses a rare sighting of a leather-back turtle nesting on the beach. But when the turtle$1 (Bs eggs are stolen, events take a dark and dangerous turn. Can Silver and her new friends track them down before it's too late? It$1 (Bll mean journeying into the heart of the jungle $1! =s
Keywords: Adventure -- Adventure